Freedom suite: la libertà in prima persona, a passo di danza jazz - Franzoso, Giacomo (Scenari, 2021)
The couple jazz and freedom is well established in modern culture: jazz is a music that makes one feel free, or sets him free. The famous works The Freedom Suite by Sonny Rollins, We Insist! Freedom Now Suite by Max Roach and It’s Freedom by Duke Ellington, are a starting point to advance a possible definition of freedom, with the language of jazz and the musical style of suite. Allusively speaking, if jazz is really free music, so freedom can introduce itself, and talk about itself thorough the analysis of melodies and lyrics, using the canon of this music, and defining some elements to subsequently interpret its meaning. Although that is only partially possible, this essay tries to recognize some analogies between the described works. These ones give different reading levels for the word freedom, and suggest various interpretations of it in artistic and musical, social and political, ethical and spiritual keys, by a dimension that can be now personal now collective, and universal.